A Regional Analysis of Supply Chain Management in India’s Defense Sector: The Case of Gwalior, Madhya Pradesh - Sharma, Sandeep; Chaurasiya, Ravi; Mohite, Rohit; Akre, Sandesh (International Journal of Strategic Studies, 2025)
Effective supply chain management (SCM) is crucial for India's defense sector to ensure operational readiness and national security. However, persistent challenges in inventory control and logistics coordination continue to impact efficiency. This study examines the supply chain management (SCM) dynamics in Gwalior, Madhya Pradesh, which holds strategic potential due to industrial zones such as Malanpur and Banmore. Despite this, local contribution to defense procurement remains limited, as evident in the Jabalpur Vehicle Plant's sourcing of only 10% of components from state vendors—primarily due to technological and quality constraints. Through field interviews, surveys, and stakeholder consultations, the research identifies critical factors influencing supply chain management (SCM) performance, including technology adoption, infrastructure readiness, and quality compliance. The study highlights the potential of local micro, small, and medium enterprises (MSMEs) to enhance their capabilities by leveraging national initiatives such as "Make in India" and "Atmanirbhar Bharat." Key recommendations include developing digital skills, investing in ERP systems, and providing stronger policy support to facilitate the better integration of MSMEs into the defense supply chain. The findings also emphasize the importance of collaboration among government agencies, private industry, and research institutions to address bottlenecks and promote innovation. By focusing on Gwalior's regional context, this study offers actionable insights that can inform broader reforms in India's defense logistics ecosystem, helping to build a more agile, resilient, and self-reliant supply chain architecture across the country.